Modeling the link beam behavior to evaluate its performance according to FEMA 356 and calculating the target displacement of performance levels - Mohammad Ali Fathali; Seyed Rohollah Hoseini Vaez; Ehsan Dehghani (پژوهش‌های زیرساخت‌های عمرانی, 2019)
The presence of the link beam in eccentrically braced frames is primarily responsible for different behavior of this frame with other structural systems. In accordance with the FEMA 356, for the evaluation of the performance of the link beam in all of its behavioral areas, the plastic rotation of the plastic hinges is required. In many studies, for the modeling of the link beam, at two end of an elastic beam, two bending and shear plastic hinge are modeled simultaneously. In this method, it is not possible to model the generalized behavior of the beam and evaluate its performance in accordance with the FEMA 356. In this paper, a new method for modeling the behavior of the link beam is presented. According to this method, at the location of the joint formation, only one flexural joint is modeled and its behavior is determined to be equivalent to the behavior of the link beam. In addition to presenting a new method for link beam modeling, the process of calculating the target displacement for each level of performance is described. OpenSees software has been utilized to model and analyze. Finally, for verifying the process of calculating the target displacement of performance levels and the proposed modeling method, the results of nonlinear static analysis of a 2D eccentrically braced frame are presented and compared with the results of the SAP2000. Comparison of the results confirms the accuracy of the modeling and the process of calculating the target displacement.